DESIGN AND BUILD A PROTOTYPE UNMANNED CAR BASED ON ROAD MARKINGS WITH THE LINE DETECTION METHOD - Luqman Hardianto; Miftachul Ulum; Achmad Fiqhi Ibadillah (Merdeka Malang University, 2021)
Safety is a necessity in any case, as is driving. Many motorists today ignore safety in driving. Based on this innovation is needed in driving safety, automatic steering cars can be one of the driving safety solutions. This is because the automatic steering car uses a technological approach from various aspects ranging from deep learning, computer vision, sensor fusion, localization, control, unit path planning. In this discussion, the implementation of the line detection algorithm uses the hough transform and power steering methods. The results of the application of this method require a method to recognize the road markings with other things that are symmetrical in shape like a line, can be a shadow of a pole, a road divider, and so forth. Because the parameters of this method can only be used in ideal conditions. The overall application of this method successfully detects road markings with an accuracy of 75%